ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM KABUPATEN TAPANULI SELATAN - Sarmiana Batubara; Putri Bunga Meiliana (Jaksya: Jurnal Akuntansi Syariah, 2023)
The performance of MSMEs in general varies considerably from year to year. This condition is due to the fluctuating level of MSME output growth in each year. One problem that is often faced by MSME actors is financial management. The impact of neglecting financial management may not be obvious, but without effective accounting methods, businesses that have prospects for success can become bankrupt. Various other limitations faced by MSMEs ranging from educational backgrounds that are not familiar with accounting or bookkeeping, the absence of sufficient funds to hire accountants or buy accounting software to facilitate the implementation of accounting books. This research is expected that micro and small enterprises (MSMEs) are used as tools for using information for decision making in credit applications and calculating taxes. The sample of this study is the guided SMEs in Tapanuli Selatan City Cooperative and SME Market Empowerment Service in 2018. This research method uses multiple linear regression analysis. The results of the study stated that partially the level of education, duration of business and accounting training had a significant effect on the use of accounting.